The Battle Between WeChat Pay and Alipay on Strategy Level - Dong, Xinyi (2017)
In the increasingly changing business world, solely adopting industry level analysis or firm level analysis might be inefficient to explain how certain company obtain sustainable competitive advantage and achieve success in market battle. In this case, to better understand the battle between Alibaba Group and Tencent in third-party payment industry, this dissertation conducts a conjunct analysis including both external and internal investigation. Results indicate that support infrastructure and specific organizational routine could be the most vital firm resources in generating Tencent’s sustainable competitive advantages, and the intrinsically high user stickiness of instant message industry provides Tencent with a protective barrier to maintain its advantages as well. Further quantitative researches could help generalize these findings and figure out the most decisive factors among all exterior and interior aspects, which could facilitate efficient strategy planning.